Does Foodservice industry care about CSR? A study in Portugal and Ukraine - Sokil, Oksana (2020)
The purpose of the article is to compare the CSR perception level of the food service industry in Portugal and Ukraine. The main goal of the study is to find the attitudes in Portugal and in Ukraine towards CSR. Additionally, two hypotheses were formulated to understand the possible relation between (1) the financial situation and (2) the duration of the company with the awareness level about the CSR concept. A quantitative approach, using questionnaires, was adopted to survey using a sample of 201 representatives of SMEs in the foodservice sector (101 Portuguese and 100 Ukrainian), in 2019. Descriptive statistics and Spearman test were used to analyze the data. The present work demonstrates a significant correlation between the financial situation of the company and the CSR awareness level of leadership. Furthermore, the research shows that activities related to the economic sphere and CSR workplace policy among food sector companies in Ukraine and Portugal are developed to a great extent. From this point of view, we can state, that the publication of the article is one of the results and supported by grant project KEGA 005SPU-4/2019 “Theory and Practice of the International Management and Entrepreneurship in Multicultural Environment”. In this study, two different countries were chosen (Portugal and Ukraine), which are different in culture, history, and economic background. The paper focused on the food service industry and contributes to the ongoing debate about the SMEs and its involvement with CSR. It also helps schools to identify plans in CSR policy and topics for future research.